The effect of L-carnitine supplementation on anthropometric and malnutrition status in acute ischemic stroke patients: a triple-blinded randomized clinical trial - Samaneh Hajjarzadeh; Mehdi Zarei; Shahram Rafie; Davood Shalilahmadi; Majid Karandish (BMC Nutrition)
Abstract Background Malnutrition is a significant challenge in stroke patients, affecting both rehabilitation and independence. This study aims to evaluate whether early L-carnitine supplementation can effectively improve anthropometric parameters and malnutrition status in acute-phase ischemic stroke patients to mitigate the catabolic state. Methods Eighty-two first-ever ischemic stroke patients were randomly assigned to either the L-carnitine group (1000 mg three times/day for seven consecutive days) or the matching placebo group. The study outcomes based on intention-to-treat analyses included changes in weight, body mass index, triceps skinfold thickness, mid-arm circumference, mid-arm muscle circumference, arm muscle area, calf circumference, serum ALB and malnutrition status over the seven-day treatment protocol. Malnutrition was assessed based on the serum ALB concentration, mid-arm muscle circumference, and triceps skinfold thickness. Analysis of covariance (ANCOVA) was applied for assessing the between-group changes along with adjusting the baseline mean value effect. Results Patients receiving L-carnitine had significantly lower changes in terms of weight, body mass index, triceps skinfold thickness, mid-arm circumference, mid-arm muscle circumference, and calf circumference than did those in the placebo group. After the intervention, the placebo group experienced a significantly greater reduction in the mid-arm muscle circumference indicator (P < 0.001). The between-group change in the serum ALB concentration significantly increased in the L-carnitine group (P = 0.001). Moreover, the L-carnitine group was less malnourished than the placebo group [17 (41.5%) vs. 30 (73.2%), respectively; P = 0.01], after the intrvention. The “recovery” frequency was significantly greater in the L-carnitine group (18 (43.9%) vs. 3 (7.3%), P < 0.001) than the placebo group. Conclusions Early L-carnitine supplementation effectively improves anthropometric indices and malnutrition, muscle wasting, and rapid weight loss in acute ischemic stroke patients, highlighting its potential as a supportive nutritional therapy during stroke rehabilitation. Trial registration The current clinical trial study was registered in the Iranian Registry of Clinical Trials (registration code: IRCT20221206056734N1) at 2023-02-11.